(untitled) (The Research of Medical Science Review, 2024)
Beetroot and other colorful root vegetables exhibit strong antioxidant activity due to the presence of polyphenol compounds. Epidemiological research has demonstrated a negative correlation between fruit and vegetable diet and the risk of developing human cancer due to the presence of antioxidant phenolic compounds. This study was conducted to evaluate the antioxidant activity of red beetroot, its total phenolic content and product development. Three types of beetroot products were developed including beetroot chips, beetroot sauce and muffins (beetroot colored). The antioxidant and proximate analysis of the beetroot products was conducted. Beetroot powder antioxidant activity was measured using the DPPH (2,2-diphenyl-1-picrylhydrazyl) technique and a UV-Vis spectrophotometer. The results of proximate analysis showed that beetroot is particularly high in fiber and sugars. The antioxidant analysis of beetroot powder showed that it is rich in phytochemicals and thus exhibits strong antioxidant potential. The results of the study indicate that red beetroot contains significant amount of polyphenols due to which it exhibits anti-inflammatory, hepatoprotective, anti-cancer properties. Hence, it can be used as a functional food with powerful antioxidant and anti-inflammatory properties.